Blood donor notification and counseling: Our experience from a tertiary care hospital in India - Kotwal, Urvershi (Asian J Transfus Sci, 2015)
AIMS: To evaluate the response rate of transfusion-transmissible infection (TTI)-reactive donors after notification of their abnormal test results for the year 2012. MATERIALS AND METHODS: This study is an observational descriptive study performed in our department over a period of 1 year. We evaluated the response rate of TTI-reactive donors after notification of their abnormal test results over 1 year as per the existing strategy (three telephonic and two postal communications). RESULTS: During the study period, among the annual donation of 15,322 units, 464 blood donors were found to be seroreactive. Of these 464 seroreactive cases, 47 were HIV positive, 284 were reactive for Hepatitis B surface antigen (HBsAg), 49 were Hepatitis C (HCV) positive and 84 were VDRL reactive. The TTI-reactive donors (464) for various markers were contacted: 229 (49.4%) telephonically and the remaining 235 (50.6%) not contacted on phone were informed by post. Of the 229 contacted donors, the response rate was 98.2% as only 225 donors reported (221 on the first, three on second and one on the third call) for one to one counseling. The remaining four non-responders were - one HIV and three HBsAg reactive. The remaining 235 (50.6%) reactive donors did not respond to any communication. CONCLUSION: Donor notification and post-donation counseling are an essential aspect of the blood bank that entails provision of information on serological status, assess the impact of test results on the donor and finally referral for medical care. As in our data only 49.4% of the blood donors could be contacted successfully, incomplete demographic details was the major limiting factor in communicating with rest. Of the 229 contacted donors, the response rate was 98.2%. A large majority (94.75%) of the notified donors in our study contacted their health care provider when given clear instructions to do so. These results are encouraging because they indicate that a major element of the notification message is acted upon when it is worded clearly. The very high response rate of the contacted donors ensured their concern for knowing their test result status.